PENGEMBANGAN AGROWISATA BERBASIS TANAMAN DURIAN DI DUSUN SELOKURUNG KABUPATEN MALANG - Moch Khamim (Jurnal Pengabdian kepada Masyarakat, 2020)
Selokurung Hamlet is one of the hamlets in Kaumrejo Village, Ngantang District which has a lot of potential in agriculture, one of the superior potentials that can be relied on is durian. The durian fruit produced is of high quality in large quantities, besides that the durian fruit produced has been able to be marketed in various regions in East Java. But what is very unfortunate is that not many people are interested in developing this agriculture, on the other hand the durian farming business in Selokurung Hamlet still has not received much touch of technology and management of modern and adequate durian farming business, so it is still very possible to be developed better again, which in the end was able to make durian farming a source of strength for the welfare of the people in Selokurung Hamlet.